Development and optimization of magnetic nanoparticles for targeted therapy. (September 2016) - Patitsa, M.; Tziouni, A.; Kordatos, K.; Verganelakis, D.A.; Klinakis, A.
Abstract : Introduction: Nanoparticles have a unique role in the field of nanomedicine since they can be used in an extensive range of applications including disease diagnosis, drug delivery and therapy. Purpose: This study aims at the identification of the optimal magnetic nanoparticle for drug delivery and imaging of tumor cells. A wide variety of nanoparticles have been characterized with respect to drug loading and release, magnetic steering, MR imaging, interaction with cell membranes, in vitro therapeutic efficacy and cytotoxicity and in vivo biocompatibility. The focus of this study is about breast cancer. Materials and methods: A variety of nanoparticles were produced, such as carbon nanotubes, multi-wall carbon nanotubes and processed accordingly in order to acquire magnetic properties, to encapsulate the chemotherapeutic drug and to coat them in order to protect them from the immune system and limit aggregation. To assess in vitro cytotoxicity and therapeutic efficacy human breast cancer cells MDA-MB-231 were injected into a number of mice. After an incubation period for the injected cells, nanoparticles were then injected into the mice and imaged using a 1.5 T Signa HDxt system. Results: A series of MRI experiments in mice with breast cancer demonstrated the correlation between magnetic properties, aggregation, biocompatibility, drug loading, therapeutic effect, size and surface chemistry of the injected nanoparticles. Depending on the desired properties of the nanoparticles different types could be optimal. Conclusion: The development and optimization of magnetic nanoparticles for targeted therapy of breast cancer cells generated a wide range of interesting results.